2015
DOI: 10.1088/1612-2011/13/2/025604
|View full text |Cite
|
Sign up to set email alerts
|

The synergistic effect on osteogenic differentiation of human mesenchymal stem cells by diode laser-treated stimulating human umbilical vein endothelial cells

Abstract: Angiogenesis plays an important role in determining the biostimulation of bone regeneration, in either new bone or blood vessel formation. Human umbilical cord cells (HUVECs) are important effector cells in angiogenesis and are indispensable for osteogenesis and for their heterogeneity and plasticity. However, there are very few studies about the effects of HUVECs on diode laser-stimulated/regulated osteogenesis. In this study, we used diode laser as a model biostimulation to examine the role of HUVECs on lase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Alkaline phosphatase (ALP) is well established in the literature as an early marker for osteogenesis, 22,36,37 and was thus chosen as the most appropriate method for assessing the osteogenesis of MSCs. Using traditional co-culture methods, the complexity of cell–cell interactions is apparent.…”
Section: Resultsmentioning
confidence: 99%
“…Alkaline phosphatase (ALP) is well established in the literature as an early marker for osteogenesis, 22,36,37 and was thus chosen as the most appropriate method for assessing the osteogenesis of MSCs. Using traditional co-culture methods, the complexity of cell–cell interactions is apparent.…”
Section: Resultsmentioning
confidence: 99%
“…In the past, many studies have confirmed that the cytokines released during angiogenesis can effectively promote the differentiation of surrounding cells [ 51 ]. However, the crosstalk between hDPSCs and HUVEC can direct the differentiation of stem cells toward stem cells that later wrap osteo-/odontogenesis to form functional hard tissue [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of human tissues show that endothelial cells in normal surrounding tissue express OPG. Moreover, HUVEC and other endothelial cells both expressed OPG during angiogenesis [ 51 ]. Therefore, the above results not only indicate that Si plays a role in enhancing angiogenesis, but also stimulate HUVEC to secrete a variety of cytokines that can assist odontogenic differentiation, which is beneficial to endodontic regeneration engineering.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When compared to their correlating control groups, DPCL and DCS increased cellular proliferation by 1.31- and 1.43-times after seven days of cell culturing, respectively. After cell adhesion and proliferation, cells can not only secrete even more ECM proteins, such as FN and Col I, but can also respond to various ECM components that help to maintain homeostasis [ 43 ]. In general, enhanced interactions between cells and ECM result in better cellular adhesion, which could trigger cell signaling cascades that up-regulate the phosphorylation of several proteins, such as focal adhesion kinase [ 34 ], providing an synergistic effect on cellular proliferation.…”
Section: Resultsmentioning
confidence: 99%